Fermented cottonseed and rapeseed meals outperform soybean meal in improving performance, rumen fermentation, and bacterial composition in Hu sheep - Rehemujiang, Halidai; Yusuf, Hassan Ali; Ma, Tao; Diao, QiYu; Kong, Luxin; Kang, Lingyun; Tu, Yan (Frontiers in Microbiology, 2023)
Background This study examined the effects of substituting cottonseed meal (CSM) or rapeseed meal (RSM) for soybean meal (SBM) on Hu sheep performance, rumen fermentation, and bacterial composition. 51 four-month-old indigenous male Hu sheep with starting body weights of 22.51 ± 2.84 kg and similar origins were randomly assigned to three treatments; (1) non-fermented total mixed ration (TMR) with SBM (CK), (2) fermented TMR containing CSM (F-CSM group), and (3) fermented TMR containing RSM (F-RSM group). Results The three groups’ intake of dry matter differed significantly (p < 0.05). In terms of average daily gain, the F-RSM group outperformed the CK and F-CSM groups (p < 0.05). The pH of the rumen was substantially lower in the CK group than in the F-CSM and F-RSM groups (p < 0.05), and the F-CSM group had greater amounts of volatile fatty acids (VFA) than the F-RSM and CK groups. In comparison to the CK group, the microbial crude protein yield was significantly higher in the F-CSM and F-RSM groups (p < 0.05). The F-CSM group significantly outperformed the F-RSM group of pepsin and cellulose enzyme activity (p < 0.05). The relative abundance of Bacteroidetes was greater in the CK and F-RSM groups compared to the F-CSM group (p < 0.05). In comparison to the other groups, Firmicutes were less abundant in the CK group (p < 0.05). Prevotella was present in a higher relative abundance in the F-CSM and F-RSM groups than in the CK group (p < 0.05). Prevotella was greater in relative abundance in the F-CSM and F-RSM groups than in the CK group (p < 0.05). The relative abundances of Veillonellaceae_UCG-001 and Lachnospiraceae_XPB1014 correlated with rumen butyric acid content and NH3-N content (p < 0.05). Gene function prediction revealed that replacing SBM with F-CSM or F-RSM in the diet of Hu sheep can promote glycan biosynthesis and metabolism. Conclusion The replacement of F-CSM and F-RSM for SBM has an influence on the richness and diversity of rumen bacteria at the phylum and genus levels. Replacement of SBM with F-CSM increased VFA yield and further promoted the performance of Hu sheep.